Microsatellite DYS385 polymorphism among the tai and mon-Khmer speaking populations of Northern Thailand - Jatupol Kampuansai (2018)
Microsatellite DYS385 is a highly polymorphic marker in the Y chromosome. It has been used for investigating population genetic structure and personal identification in various ethnic groups of the world. This research aimed to analyze the microsatellite DYS385 polymorphism among 9 Tai and 11 Mon-Khmer speaking populations of northern Thailand. Fifty-six different haplotypes were found in 453 samples from 20 populations. Haplotype diversities and discrimination powers of populations belonging to the Tai linguistic family was higher than those of the Mon-Khmer group. Genetic affinities based on DYS385 variation do not conform to linguistic classification but a fraction of genetic divergence patterns can be explained by geographic distances.